PENGEMBANGAN GOOGLE SITES BERBANTUAN APLIKASI SEKOLAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII POTENSI EKONOMI LINGKUNGAN - Najma Ainur Rizkiyah Aryma; Lamijan Hadi Susarno; Utari Dewi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The integration of digital technology into learning continues to expand as an effort to enhance both the quality of instruction and student learning outcomes. At one junior high school in Surabaya, however, the school application has primarily been utilized for assessment purposes, leaving its potential as a digital learning resource largely untapped. In response to this condition, this study developed a Google Sites-based learning resource integrated with the school application for the Environmental Economic Potential topic for seventh-grade students. The development employed the Research and Development approach using the Lee & Owens model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. Product feasibility was determined through expert validation, while its effectiveness was examined using a Non-Equivalent Control Group Pretest–Posttest Design. Data were collected through observations, interviews, expert validation, student response questionnaires, and learning achievement tests, and were analyzed using descriptive percentage analysis and an Independent Sample t-test. The developed product was rated as highly feasible, with expert validation scores ranging from 97% to 100%, and received highly positive responses from students in both the small-group trial (93%) and the field trial (97%). The effectiveness test yielded a significance value of 0.000 (<0.05), indicating a statistically significant difference in learning outcomes between the experimental and control groups. These findings demonstrate that integrating Google Sites with the school application optimizes the application's function as an accessible digital learning resource while contributing to improved student learning outcomes. ABSTRAK Penggunaan teknologi digital di lingkungan sekolah belum selalu diikuti oleh pemanfaatan yang optimal dalam proses pembelajaran. Pada salah satu SMP di Surabaya, aplikasi sekolah masih lebih banyak difungsikan sebagai media asesmen sehingga potensinya sebagai sumber belajar digital belum dimanfaatkan secara maksimal. Berangkat dari kondisi tersebut, penelitian ini menghasilkan pengembangan sumber belajar berbasis Google Sites yang terintegrasi dengan aplikasi sekolah pada materi Potensi Ekonomi Lingkungan untuk peserta didik kelas VII. Pengembangan dilakukan melalui pendekatan Research and Development dengan model Lee & Owens yang mencakup tahapan Analysis, Design, Development, Implementation, dan Evaluation. Kelayakan produk dievaluasi melalui validasi ahli, sedangkan efektivitasnya diuji menggunakan desain Non-Equivalent Control Group Pretest–Posttest Design. Pengumpulan data melibatkan observasi, wawancara, angket respons peserta didik, validasi ahli, dan tes hasil belajar, kemudian dianalisis menggunakan analisis deskriptif persentase serta Independent Sample t-test. Produk yang dikembangkan memperoleh penilaian sangat layak dengan hasil validasi ahli sebesar 97–100%, disertai respons peserta didik yang sangat positif pada uji kelompok kecil (93%) maupun uji lapangan (97%). Pengujian efektivitas menunjukkan nilai signifikansi 0,000 (<0,05), yang mengindikasikan adanya perbedaan hasil belajar yang signifikan antara kelas eksperimen dan kelas kontrol. Hasil tersebut memperlihatkan bahwa integrasi Google Sites dengan aplikasi sekolah mampu mengoptimalkan fungsi aplikasi sebagai sumber belajar digital yang mudah diakses sekaligus berkontribusi terhadap peningkatan hasil belajar peserta didik.